Boldness-mediated habitat use tactics and reproductive success in a wild large herbivore. (November 2018) - Bonnot, Nadège C.; Goulard, Michel; Hewison, A.J. Mark; Cargnelutti, Bruno; Lourtet, Bruno; Chaval, Yannick; Morellet, Nicolas
Abstract : The balance between resource acquisition and risk avoidance should vary according to personality type, with potential knock-on effects for fitness. Although previous studies have suggested a link between boldness and fitness components, little evidence is available on the behavioural mechanisms mediating this relationship in the wild. Because habitat use is the outcome of the trade-off between the costs and benefits associated with using each habitat type, we evaluated between-individual differences in habitat use of 64 GPS-collared female roe deer, Capreolus capreolus, using multinomial logit mixed models. To investigate whether deer differed in their habitat use tactics in relation to their personality type and their annual reproductive success, we assessed the link between individual habitat use patterns, boldness (measured as the strength of behavioural responsiveness to handling) and annual reproductive success (measured by the presence/absence of fawns at heel during autumn). Although daily and seasonal variations in the risk–resource landscapes clearly drove patterns of habitat use, individuals adopted contrasting habitat use tactics depending on their position along the shy–bold gradient and their reproductive status. Shy individuals occupied safer woodland more frequently, even at night when risk is lower. In contrast, bold individuals were better able to exploit rich open habitats. When this included mature autumn crops, these females weaned more offspring. Finally, irrespective of personality type, females that used meadows more often also achieved higher annual reproductive success. Overall, we demonstrate that individuals express divergent habitat use tactics as a function of their ability to avoid exposure to risk and their annual reproductive success. Highlights: We measured habitat use, boldness and reproductive success in 64 female roe deer. Spatiotemporal variations in the risk-resource trade-off shape deer habitat use. The way individuals use their environment also depends on their personality type. Differences in habitat use between personalities are linked to reproductive success. Individual habitat use tactics mediate the personality – fitness link in the wild.